Oral vinorelbine versus etoposide with cisplatin and chemo-radiation as treatment in patients with stage III non-small cell lung cancer: A randomized phase II (RENO study). (September 2019) - Isla, Dolores; De Las Peñas, Ramón; Insa, Amelia; Marsé, Raquel; Martínez-Banaclocha, Natividad; Mut, Pilar; Morán, Teresa; Sala, María Ángeles; Massuti, Bartomeu; Ortega, Ana Laura; Jurado, José Miguel; Gómez-Codina, José; et al.
Highlights: Globally adverse events grade 3/4 per cycle were fewer in the vinorelbine and cisplatin arm than in the etoposide and cisplatin arm. Median progression free survival was similar in both arms. Preliminary median overall survival was 30 months in the vinorelbine and cisplatin arm and 31.9 months in the etoposide and cisplatin arm. Abstract: Objectives: Concomitant chemo-radiation is the standard treatment for unresectable stage III non-small cell lung cancer (LA-NSCLC). The aim of this study was to assess the safety and efficacy of oral vinorelbine and cisplatin (OVP) compared with etoposide and cisplatin (EP), both in combination with radiotherapy, in this setting. Material and methods: An open-label, randomized phase II trial was undertaken including 23 hospitals in Spain. Adults with untreated unresectable stage III NSCLC were randomized1:1 to receive: oral vinorelbine (days 1 and 8 with cisplatin on day 1 in 3-week cycles; 2 cycles of induction, 2 cycles in concomitance) or etoposide (days 1–5 and 29–32 with cisplatin on days 1 and 8 in 4-week cycles; 2 cycles in concomitance). Both groups received concomitant radiotherapy 2 Gy/day (66 Gy). The primary endpoint was progression free survival (PFS). Results: One hundred and forty patients were enrolled. Sixty-nine patients received OVP and 71 received EP. Globally adverse events grade 3/4 per cycle were fewer in the vinorelbine arm (19.4%) than in the etoposide arm (62.6%) ( p < 0.001). One patient (1.5%) in the OVP arm and 12 pts (17.6%) in the EP arm presented esophagitis grade 3/4 ( p = 0.002). Median PFS was similar in both groups (10.8 [95% CI 7.7–13.8] and 9.6 months [95% CI 4.4–14.8]; p = 0.457, respectively). Preliminary median overall survival was 30 months in the OVP arm and 31.9 months in the EP arm ( p = 0.688). Conclusions: Our findings show that OVP could be considered a standard combination with similar efficacy and better safety profile for the treatment of LA-NSCLC patients.